The compliant effect of controlled spine on interaction with the ground in quadruped trotting. (January 2020) - Li, Zhang; Tan, Yuegang; Wu, Ping; Zeng, Shun
The spine plays important roles in the quadruped locomotion. These effects not only stand out in high-speed gait but also function in low-speed gait, especially the transition gait – trotting gait. In order to investigate the effects of the spine on the motion performance of the quadruped trotting, the spine with two joints is applied into the structure of the quadruped robot. This structure is inspired from the analyses for the canine, which imitates the configuration of thoracic vertebra, front lumbar vertebra and hind lumbar vertebra. Different from the quadruped robot with the passive spine or the active spine by inputting position, a compliant control is applied to the spinal joints. The feature of force control not only possesses the soft feature of the passive spine but also has the advantage of enlarging the motion ability. In the simulation process, a large amount of analyses are carried out including the influence of the control parameters of the controlled spine, the comparison with the quadruped robot with rigid torso and the gait simulation when the robot moves on the flat ground and across an obstacle. The results reveal that the controlled spine has an excellent compliant effect on the interaction with the ground. It contributes to reducing the ground reaction forces; meanwhile, the compliant effect is beneficial for improving the stability. By establishing the prototype robot and performing the motion experiment, the compliant effect of the spine is proven effective.